EFISIENSI USAHATANI DAN PEMASARAN WORTEL (Daucus carota L) DI KECAMATAN SEPULUH KOTO KABUPATEN TANAH DATAR - Putri, Mita Amanda; Dang Sri Chaerani; Esa Diya Wahyuni (Jurnal Research Ilmu Pertanian, 2021)
The purpose of this study is as follows: 1). Analyzing the efficiency of carrot farming (Daucus carota L.) in District Ten Koto Tanah Datar District 2). Analyzing marketing efficiency in carrots (Daucus carota L.) in Sepuluh Koto District, Tanah Datar District. This research uses descriptive qualitative and quantitative methods with population criteria are (1) Farmers who carry out carrot farming activities in the planting season from April to August 2019, (2) Land area cultivated at least 0.25 Ha, (3) Land under cultivation alone. Based on these criteria there are 53 people so that the entire population that meets the criteria is sampled. Data collected in the form of primary data and secondary data. Data   analysis   was   carried   out   qualitatively   and   quantitatively. Qualitative analysis is used to find out the general picture of carrot farming and marketing, while quantitative analysis is carried out to find out about cost structure and revenue analysis and marketing efficiency seen from the marketing margin, farmer's share and the ratio of profits to marketing costs. This research was conducted in July to August 2019. Based on the results of the study it can be concluded that: 1). Carrot farming in the District of Ten Koto is worth the effort, this is evidenced by the R / C value obtained at 2.16. 2). There are 2 patterns of marketing channels with different final destination markets, namely Marketing Channel I (Farmers-PPD-PB-Pasar Raya Padang Retailers and West Pasaman) and Marketing Channel II (Farmers - PB - Long Strait Retailers and Padangsidempuan). The marketing functions performed on the marketing channel in the delivery of carrots to consumers have been effective. The most efficient channels are I.a marketing channels with a marketing margin of Rp.4,000.00; farmer's share of 50.00% ¸ and the profit-to-marketing ratio is 2.48 with a sales volume of 57,895 kg.